Technology theory in international relations: software, hardware, and the problem-solving human - Hazan, Bernardo Futuro Rodrigues (2020)
In this paper we intend to develop a Theory of Technology (TT) for International Relations. Due to its relevance to this knowledge area, we develop Technology Theory mostly in comparison with Practice Theory in IR, although we bear a different ontology and a different concept of human being, of language, and of learning. Software and Hardware are important concepts in Technology Theory. They are considered to be the outcome of Humans in their solving problems they face routinely. When considering Practice Theory, we: 1) introduce an operative concept of practice; 2) work an understanding of the learning process that has influenced this theoretical branch; 3) make the hypothesis that the tendency to disregard as central Structure and Agency in Practice Theory might be related to the Constructivist-Postmodernist debate regarding this topic in the 1990\'s. As a ground to build Technology Theory (and its relation to Language and to Deontic Powers), we make considerations Searle\'s Speech Act Theory and Berger and Luckmann\'s Symbolic Universes. We work some of the conceptualizations Structure has had in IR, so to define the Structure of Technologies. The Structure of Technologies is the set of procedural deontic relations among technologies. There is a straightforward typology of software (software-skill, software-role, software-organization), which can be integrated in clusters of technology. We develop an understanding of the learning process that differentiates itself from the classroom-model and from the Lave and Wenger\'s Legitimate Peripheral Participation model: learning as a problem-solving activity. We consider that this appraisal towards learning allows for the configuration of non-cooperative communities of technology, which in turn may explain homogeneity even between non-cooperative collectivities.